Combined Forward-Backward Asymmetry Measurements in Top-Antitop Quark Production at the Tevatron - Aaltonen, T. (2018)
The CDF and D0 experiments at the Fermilab Tevatron have measured the asymmetry between yields of forward- and backward-produced top and antitop quarks based on their rapidity difference and the asymmetry between their decay leptons. These measurements use the full data sets collected in proton-antiproton collisions at a center-of-mass energy of s=1.96 TeV. We report the results of combinations of the inclusive asymmetries and their differential dependencies on relevant kinematic quantities. The combined inclusive asymmetry is AFBtt̄=0.128±0.025. The combined inclusive and differential asymmetries are consistent with recent standard model predictions.